Interviews with artists: a virgin patch of fertile content - Veras, Eduardo Ferreira (PORTO ARTE: Revista de Artes Visuais, 2018)
Based on the finding that the use of interviews in studies has been disseminated in the field of Art History, Theory and Criticism, this article seeks to warn against the risks of engaging in naive and unsubstantialted approaches, specially when analyzing the material produced. In order to do so, it establishes a premise – regarding the sometimes tense relationship between artists’ work and their discourse – and suggests two methodological approaches: content analysis as used in Social Sciences and Oral History. Finally, it points out the need to discuss academic-scientific and similar publications’ option for presenting interviews with artists as an autonomous text genre.